(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
This article examines the role of phraseology in linguistics, its importance in representing popular culture through fixed expressions, and its role in providing semantic richness in language. The types of phraseological units and their peculiarities as means of expression are analyzed, and cultural experiences are also taken into account.